Virulence markers, phylogenetic evolution, and molecular techniques of uropathogenic Escherichia coli - Etefia U Etefia; Solomon A Ben (Wolters Kluwer Medknow Publications, 2020)
Urinary tract infections are very significant public health concerns globally with most of them being caused by uropathogenic Escherichia coli (UPEC). The wide range of genetic makeup of UPEC due to the acquisition of specialized virulence genes located on mobile genetic elements called pathogenicity islands is the rationale behind colonization of the urinary tracts of humans as against diarrheagenic E. coli pathotype. Indebt understanding of the virulence mechanisms and pathogenesis of UPEC lies in the knowledge of the molecular techniques of UPEC which have advanced tremendously. This review has carefully summarized the unique virulence markers, the phylogenetic evolution, and molecular techniques used in the studies of pathogenesis and virulence of UPEC.